Experimental Study on Residual Bearing Capacity of Existing Prestressed Concrete Hollow Slab Beam. Issue 2 (January 2021) - Wang, Baoqun; Xing, Dejin; Chen, Chengyong; Tian, Zhongnan; Xu, Gangnian
Abstract: Through the reconstruction and expansion of expressway, it has become the new normal of expressway construction in China to improve the traffic capacity and operation service level of the existing road. However, the reconstruction and expansion of expressways are faced with problems such as the degradation of the existing bridge performance and the original design bearing capacity that can't meet the current load standards, which restrict the full utilization of the existing expressway bridges. Based on the reconstruction and expansion project of Beijing-Shanghai Expressway (Shandong section), this paper selects the prefabricated and prestressed concrete (PC) simply supported slab bridge with span of 10m and 13m. It evaluates the bearing capacity of HSB based on technical condition checking calculation and load test, and carries out the ultimate bearing capacity test at the same time. According to the checking calculation of bearing capacity and test results, it is concluded that the technical condition of the existing bridges in the expressway (Shandong section) is evaluated as class 1 prefabricated simply supported slab bridge. By adding 150mm integral cast-in-place pavement, the bending capacity of the HSB in the mid of span section meets the current load standard, while the shear capacity of supporting point section does not meet the current load standard, but the difference is within 5%. After the reconstruction and expansion of expressway, the existing bridges mainly bear the load of small vehicles, the load effect is far lower than the current load standard, the bearing capacity meets the current load standard, and can be fully utilized in its original state.